2008
DOI: 10.1016/j.acra.2007.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Structure-Function Relationships in Asthma using Multidetector CT and Hyperpolarized He-3 MRI

Abstract: Rationale and Objectives-While multiple detector CT (MDCT) and hyperpolarized gas MRI (HP MRI) have demonstrated ability to detect structural and ventilation abnormalities in asthma, few studies have sought to exploit or cross-validate the regional information provided by these techniques. The purpose of this work is to assess regional disease in asthma by evaluating the association of sites of ventilation defect on HP MRI with other regional markers of airway disease, including air trapping on MDCT and inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 26 publications
(32 reference statements)
8
125
2
Order By: Relevance
“…A recent study in an emphysema-induced canine model compared volumetric CT with 3 mm slice thickness and 3 He diffusion MRI and demonstrated very good correlation between the two modalities [41]. A further study in asthmatic patients also demonstrated good correlation between MDCT findings of airway morphology and expiratory air trapping and the presence of ventilation defects [42]. This discrepancy of our relative lack of agreement compared with this literature may well be related to the fact that we used traditional HRCT methods (with axial 1-mm slices and 1-cm gaps), thus reducing the ability to obtain better comparative images.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study in an emphysema-induced canine model compared volumetric CT with 3 mm slice thickness and 3 He diffusion MRI and demonstrated very good correlation between the two modalities [41]. A further study in asthmatic patients also demonstrated good correlation between MDCT findings of airway morphology and expiratory air trapping and the presence of ventilation defects [42]. This discrepancy of our relative lack of agreement compared with this literature may well be related to the fact that we used traditional HRCT methods (with axial 1-mm slices and 1-cm gaps), thus reducing the ability to obtain better comparative images.…”
Section: Discussionmentioning
confidence: 91%
“…Currently, ventilatory function cannot easily be extracted from CT alone (23,24); likewise, MR imaging cannot provide adequate structural information for segmental delineation (25)(26)(27). With the use of the anatomic information available from CT, we were able to quantify regional 3 He ventilation in healthy volunteers and patients with severe asthma (some of whom were treated by using bronchial thermoplasty and underwent imaging with 3 He a second time).…”
Section: Implication For Patient Carementioning
confidence: 84%
“…Eighteen subjects (18 of 60 = 30%) reported normal VDP and 42 (42 of 60 = 70%) subjects reported abnormally elevated VDP. As shown in Figure 1 for three representative subjects, volunteers with normal VDP showed small or no ventilation defects along the periphery of the lung, whereas (16) 27 (14) 28 (17) .86 (1.0) Years quit smoking 19 (15) 13 (12) 21 (15) .06 (1.0) BMI, kg/m 2 29 (4) 29 (5) 30 (4) .5 (1.0) FVC, % pred 97 (13) 100 (10) 95 (14) .18 (1.0) FEV 1 , % pred 104 (13) 106 (12) 102 (14) .28 (1.0) FEV 1 /FVC 80 (6) 80 (6) 80 (6) .78 (1.0) RV/TLC, % pred 103 (15) 104 (12) 103 (16 ADC, apparent diffusion coefficient; BMI, body mass index; BSA, body surface area; DL CO , diffusing capacity for carbon monoxide; FEV 1 , forced expiratory volume in 1 second; FVC, forced vital capacity; LA, mean fifth generation airway lumen area; 6MWD, six-minute walk distance; RA 950 , relative area of the lung parenchyma with attenuation #À950 HU; RV, residual volume; SD, standard deviation; SGRQ, St. Georges Respiratory Questionnaire; TLC, total lung capacity; VDP, ventilation defect percent; WA%, mean fifth generation airway wall area percent.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperpolarized 3 He magnetic resonance imaging (MRI) ventilation heterogeneity has been shown in patients with pulmonary diseases such as COPD (4,5), asthma (6,7), and cystic fibrosis (8). At the same time, however, preclinical or subclinical 3 He ventilation heterogeneity has also been observed in volunteers without clinical signs or symptoms of lung disease such as healthy elderly never-smokers (9), ex-smokers without airflow limitation (10), in second-hand smoke exposed adults (11), and current-smokers without disease (12).…”
mentioning
confidence: 99%